Numerical simulation and analysis of splitting tensile strength of jute/epoxy laminated composites using ANSYS Workbench 2022 - Achmad Jusuf Zulfikar; Bonar Sari Monang Naibaho; Mulia; Samuel Marpaung (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
This study investigates the mechanical behavior of jute/epoxy laminated composites when applied as external reinforcement to cylindrical concrete specimens subjected to splitting tensile stress. Natural fiber-reinforced composites, such as jute, have gained significant attention in recent years due to their environmental sustainability, low cost, and reasonable mechanical performance. The primary objective of this research is to evaluate the effectiveness of jute laminate sheathing in improving the tensile strength of cylindrical concrete structures using numerical simulation. A finite element method (FEM) approach was implemented in ANSYS Workbench 2022 to model and simulate various configurations, including specimens without laminates and with one, two, and three layers of jute/epoxy laminates. The model geometry was based on standard cylindrical specimens with a diameter of 50 mm and a height of 150 mm. Material properties were defined based on experimental data, and appropriate mesh and boundary conditions were applied. Results showed that the addition of jute laminates significantly enhanced the splitting tensile strength, with the highest increase of 241% observed in specimens with three layers. The simulation results were validated against experimental data using ANOVA, confirming a strong correlation (p = 0.5). This indicates that the ANSYS-based FEM simulation is a reliable tool for predicting the mechanical behavior of natural fiber-reinforced composites in structural applications.